Participation of myosin Va and Pka type I in the regeneration of neuromuscular junctions - Röder, Ira Verena; Rudolf, Rüdiger (PLOS ONE, 2012)
Background The unconventional motor protein, myosin Va, is crucial for the development of the mouse neuromuscular junction (NMJ) in the early postnatal phase. Furthermore, the cooperative action of protein kinase A (PKA) and myosin Va is essential to maintain the adult NMJ. We here assessed the involvement of myosin Va and PKA in NMJ recovery during muscle regeneration. Methodology/Principal Findings To address a putative role of myosin Va and PKA in the process of muscle regeneration, we used two experimental models the dystrophic mdx mouse and Notexin-induced muscle degeneration/regeneration. We found that in both systems myosin Va and PKA type I accumulate beneath the NMJs in a fiber maturation-dependent manner. Morphologically intact NMJs were found to express stable nicotinic acetylcholine receptors and to accumulate myosin Va and PKA type I in the subsynaptic region. Subsynaptic cAMP signaling was strongly altered in dystrophic muscle, particularly in fibers with severely subverted NMJ morphology. Conclusions/Significance Our data show a correlation between the subsynaptic accumulation of myosin Va and PKA type I on the one hand and NMJ regeneration status and morphology, AChR stability and specificity of subsynaptic cAMP handling on the other hand. This suggests an important role of myosin Va and PKA type I for the maturation of NMJs in regenerating muscle.
Gesehen am 14.08.2018